2018
DOI: 10.3892/or.2018.6560
|View full text |Cite
|
Sign up to set email alerts
|

ESE‑1 suppresses the growth, invasion and migration of human NSCLC cells and tumor formation in�vivo

Abstract: Lung cancer is the first leading cause of cancer‑related death in the United States. Non‑small cell lung cancer (NSCLC) is the most common type of lung cancer and is associated with a poor patient prognosis. Identification of promising molecular targets is required for the effective prevention and therapy of NSCLC. Epithelial‑specific ETS‑1 (ESE‑1) belongs to the superfamily of ETS transcription factors. The effect of ESE‑1 on tumorigenesis is controversial in several types of cancer while its role in lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The xenograft study was approved by the Animal Care and Use Committee (Ajou University, South Korea) and performed as described previously . Five‐week‐old male BALB/c nude mice were purchased from Orient Bio Inc. (Gyeonggi, South Korea).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The xenograft study was approved by the Animal Care and Use Committee (Ajou University, South Korea) and performed as described previously . Five‐week‐old male BALB/c nude mice were purchased from Orient Bio Inc. (Gyeonggi, South Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Stable cell lines expressing LacZ (control) and ESE-1 full-length (FL) were established by transfecting expression vectors and subsequently selecting using G418 (800 μg/mL for selection and 400 μg/mL for maintenance) as described previously. 31…”
Section: Cell Culture and Established Stable Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Furthermore, many studies have reported that inhibition of cell migration decreases tumor growth in multiple cancers. [16][17][18] Therefore, it is important to elucidate the cellular basis and molecular mechanisms of β 2 -GPI function in antitumorigenesis. The present study aims to explore the specific regulatory domain and intracellular signaling of β 2 -GPI with a potential for antimelanoma progression.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that abnormal cell migration and proliferation are closely related to carcinogenesis . Furthermore, many studies have reported that inhibition of cell migration decreases tumor growth in multiple cancers . Therefore, it is important to elucidate the cellular basis and molecular mechanisms of β 2 ‐GPI function in antitumorigenesis.…”
Section: Introductionmentioning
confidence: 99%